Socio-Economic Factors in Compliance with PBB-P2 Payments in Kasongan Lama Subdistrict, Katingan Regency - Afrizal Afrizal; Riban Satia; Sadar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2026)
This study aims to analyze the level of compliance in paying Rural and Urban Land and Building Tax (PBB-P2) and to identify factors influencing the optimization of local tax revenue in Kasongan Lama Subdistrict, Katingan Regency. The research employs a qualitative descriptive approach utilizing secondary data from PBB-P2 revenue realization reports for the period 2023–2025 obtained from the Regional Revenue Agency of Katingan Regency, as well as primary data collected through field observations and interviews with tax officers and taxpayers. The findings indicate that the level of PBB-P2 payment compliance in the study area remains relatively low despite a gradual increase, reaching 10% in 2023, 15% in 2024, and 28% in 2025. The low compliance rate is influenced by several key factors, including limited public awareness of the role of taxes in regional development, household economic constraints, relatively low levels of formal education, and administrative issues such as inaccurate tax object data and limited local tax information systems. The study demonstrates that optimizing PBB-P2 revenue is not solely dependent on administrative tax mechanisms but also requires socio-economic approaches through improved tax literacy, strengthened tax object databases, and innovative payment service systems that are more accessible to the public. Therefore, efforts to enhance local tax revenue should involve integrated strategies including community education, digitalization of payment services, and incentive policies for low-income households.